Creating and capturing value from external knowledge: the moderating role of knowledge intensity. (June 2014) - Denicolai, Stefano; Ramirez, Matias; Tidd, Joe; Spieth, Patrick; Schneckenberg, Dirk; Ricart, Joan E.
<x xml:space="preserve">Abstract</x> Business model innovation (BMI) often involves the acquisition of external resources, their integration with and adaptation to internal capabilities and the exploitation of these novel combinations to create and capture value in new ways. However, studies focusing on the relationships among capabilities, BMI and firm performance are rare. In this paper, we adopt broader measures of internal and external knowledge, which include codified intangibles such as patents and copyrights, and examine the effects the combinations and interactions have on sales growth based on a dataset of 310 firms from four European countries. Using the broader measure of knowledge, we find support for the curvilinear relationship reported in studies using research and development‐intensity as a proxy. However, we also find that firms with low levels of internal knowledge benefit most from an 'optimal' investment in externally generated knowledge, but the influence on sales growth is very sensitive to the degree of external knowledge acquired. By contrast, knowledge‐intensive firms are relatively freer in defining their knowledge sourcing strategy. We discuss the implications for exploiting knowledge and complementary assets in BMI.